Effect of garlic (allium sativum) powder and neem (azadirachta indica) seed cake on cholesterol content in broiler chicken - Lonkar Vijaysing Dhansingh (Department of Poultry Science, College of Veterinary and Animal Science, 2006)
An experiment was conducted at the Department of Poultry Science to investigate the effect of dietary supplementation of garlic (Allium sativum) powder and neem (Azadirachta indica) seed cake and their combination on the performance and cholesterol content of meat and serum in broiler chicken. Two hundred and ten day-old straight run commercial broiler chicks were reared under seven different treatments with three replicates of ten chicks each. The T1 was control with standard broiler ration and garlic powder (GP) and neem seed cake (NSC) were supplemented in the basal diet to form diets T2 to T7. The experiment was carried out with two levels of GP supplementation, 0.5 per cent (T2) and 1.0 per cent (T3), two levels of NSC supplementation, 1.0 per cent (T4) and 2.0 per cent (T5) and two levels of GP and NSC combination, 0.5 per cent GP and 1.0 per cent NSC (T6) and 1.0 per cent GP and 2.0 per cent NSC (T7). The rations were made isocaloric and isonitrogenous. Chicks were reared under standard managemental conditions up to six weeks of age. The broiler starter ration was fed from zero to four weeks and finisher ration from five to six weeks of age. Results of the study revealed that, supplementation of GP at 0.5 or 1.0 per cent and NSC at 1.0 or 2.0 per cent levels and a combination of 1.0 per cent GP and 2.0 per cent NSC significantly (P≤0.05) depressed the final body weight, while a combination of 0.5 per cent GP and 1.0 per cent NSC did not influence final body weight of broilers. The cumulative body weight gain up to sixth week of age was significantly (P≤0.05) lower by supplementation of GP or NSC alone or their combination in broiler diet. The cumulative feed intake up to sixth week of age did not reveal any significant difference between treatments. But numerically lower feed consumption was recorded in T5 and T7 where NSC was included at 2.0 per cent level. Cumulative feed efficiency up to six weeks of age was significantly (P≤0.05) inferior in T7 and was superior with control group (T1) and groups T1 to T6 was in a homogenous comparable group. The per cent dressed yield, eviscerated yield, ready-to-cook yield, blood loss, feather loss and total loss in broilers were not influenced by dietary supplementation of GP and NSC alone or in combination. The per cent giblet yield of birds supplemented with 0.5 per cent GP and 1.0 per cent NSC (T6) was significantly (P≤0.05) lower, while other levels of GP and NSC and their combination did not influence the same. The weight of bursa of fabricious and spleen at sixth week of age was increased by supplementation of GP and NSC and their combination in broiler diet. The dietary supplementation of GP at 0.5 per cent and NSC at 1.0 per cent level numerically reduced the serum total cholesterol level, while in T3, T5, T6 and T7 there was significant (P≤0.05) reduction in serum total cholesterol. The supplementation of GP and NSC alone and in combination significantly (P≤0.05) reduced the breast and thigh meat total cholesterol in broilers. Supplementation of GP and NSC alone and in combination in broiler diet did not influence the serum total protein and breast and thigh meat crude protein. Livability of all treatment groups was 100 per cent. It shows that dietary supplementation of GP, NSC and their combination at the levels employed in this study had no deleterious effect in broilers. Net profit per kg body weight was reduced as a result of inclusion of GP and NSC alone and their combination in broiler diet. The results of the present study suggest that supplementation of garlic powder and neem seed cake in broiler rations is beneficial for substantial reduction in the cholesterol content of poultry meat.